Diseño de una estrategia financiera para la reactivación económica, panificadora Jeremy, Tabacundo provincia de Pichincha 2022. - Pujota, Digna A. (2022)
Panificadora Jeremy, is a microenterprise that is located in the canton of Pedro Moncayo in the "Y" of Tabacundo, in front of the police Comunidad Panamericana Norte via Cajas, was opened in the market of in 2012, by the first owner Riego Guazapas, who sold to Mr. Juan Inlago as the current owner, the sale was due to mismanagement of the company due to lack of knowledge in the implementation of strategies financial, for the economic reactivation of the business.